1988
DOI: 10.1007/bf01962355
|View full text |Cite
|
Sign up to set email alerts
|

Early prenatal diagnosis of congenital toxoplamosis using amniotic fluid samples and tissue culture

Abstract: The presence of Toxoplasma gondii in amniotic fluid was demonstrated using tissue culture in four of nine cases of congenital toxoplasmosis, whereas Toxoplasma gondii antigen was undetectable using a sensitive enzyme immunoassay technique. Parasites were identified in monolayers four days after inoculation using an indirect immunofluorescence assay. Since tissue culture may provide evidence of infection within a few days, this method is proposed for early prenatal diagnosis of congenital toxoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 4 publications
0
23
0
1
Order By: Relevance
“…Fetal blood samples must be collected in the second term of pregnancy (when the fetal immune system is functional) by experienced obstetrical teams [29], Several biological tests must be performed to verify that fetus samples are not contaminated with maternal blood, which would interfere with diagnosis of congenital infection on the basis of parasitological and serological results [1,2,[30][31][32],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal blood samples must be collected in the second term of pregnancy (when the fetal immune system is functional) by experienced obstetrical teams [29], Several biological tests must be performed to verify that fetus samples are not contaminated with maternal blood, which would interfere with diagnosis of congenital infection on the basis of parasitological and serological results [1,2,[30][31][32],…”
Section: Discussionmentioning
confidence: 99%
“…inoculation of mice [1][2][3] and on serological tests, which detect anti-toxoplasma IgG and IgM Correspondence: Dr Anne Decoster, Laboratoire St Antoine, 329 Boulevard Victor Hugo, BP 255, 59019 Lille Cedex, France.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of material obtained by chordocentesis for the diagnosis of infection of fetuses gave reliable results, especially if used for biological testing [21 ]. but we must bear in mind that chordocentesis can be used only after 20 weeks of gestation and that a period of 1-5 weeks is needed for biological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results are obtained only several weeks after inocculation. Recent studies [4,11,12] have shown human diploid fibroblast cells to be an attractive alternative to mice for isolating T. gondii because of the similar sensitivity, wider availability and higher rapidity in obtaining results.…”
Section: Isolation Of T Gondiimentioning
confidence: 99%